ARTISTIC PRODUCTION AND ITS RELATIONSHIP TO PERSONALITY TRAITS AMONG STUDENTS OF FINE ARTS INSTITUTE - Dr. Tahreer Jasim Gatea (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The upgrading of art and art process requires upgrading the methods and techniques that help students cope with the art on the scientific, technical and artistic development of the theoretical and practical level of performance requirements in order to qualify for the production of a successful and distinctive artwork.The research aims to: Identification of visual work and its relationship to the personal characteristics of the students of the Department of Art Education.